Observing and Monitoring the Urban Expansion of Makkah al-Mukarramah Using the Remote Sensing and GIS - Nuzha Al Jabri, Rayan Alhazmi (Journal of engineering sciences and information technology, 2017)
This study aims at surveying and recording land cover changes as well as urban changes in the city of Makkah al-Mukarramah throughout the period between 1992 and 2016. To achieve this purpose, the study relies on the inductive approach to monitor the urban developments, population growth and land uses through the structural schemes of Makkah al-Mukarramah along with the official reports issued from the Secretariat of Holy Makkah Municipality, the High Commission for the Development of Makkah al-Mukarramah and scientific research. It also endorses spatial analysis as its approach to extract digital data from satellite imagery to survey the temporal changes to the land covers in Makkah al-Mukarramah. These digital data, along with the final output map compositions, have been processed through the employment of two specific mapping software: ArcGIS v10.3 and ERDAS IMAGINE v14. The study at hand reached the conclusion that most of the urban developments in the city, particularly the housing and commercial developments, is centered around the Holy Mosque and in the neighboring districts in a way that demonstrates the influence of the mountainous terrain on the urban sprawling of the city across the narrow valleys to the flat urban outskirts. The study has further shed light on the changes that affected the percentage of land covers in the city throughout the period of the study. Urban use[1] of land covers in the city rose significantly from 12% of its total area in 1992 to 22.13% in 2016. On the contrary, ratio of undeveloped lands to the total area has plummeted from 42.7% in 1992 to 35.36% in 2016. This fall is due to the rise in the urban exploitation of lands and the urban growth towards the low-lying areas in the outskirts of the city, particularly the lands that circle regional highways and ring roads. With regards to the mountainous areas, it fell in ratio to the total area of the city from 41% in 1992 to 39.2% in 2016 thanks to the development projects which necessitated removing and flattening some of the rocky areas near parts of the most important sites in the holy city. Whereas the ratio of green spaces to the total area of the city has oscillated from one image to another, it hit a percentage of 3.83% in 1992 falling to 3.27% in 2016. In fact, this fluctuation stems from the variance of months that passed between the satellite imagery collection. The researchers, who conducted this study, seek to highlight the significance of employing GIS and remote sensing technologies in executing subsequent studies that are concerned with planning and predicting land cover changes and land uses in the city of Makkah al-Mukarramah.